2017
DOI: 10.1088/1755-1315/90/1/012152
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of hardening kinetics of building composites based on cement binders

Abstract: Abstract.The issue of regulation of hydraulic mineral binders hydration kinetics and development of solutions for stabilization of hydration process due to application of mineral and organic additives are investigated in this research. The article presents results of the theory and practice of hydration hardening building materials production analysis with the use of heat treatment methods, obtained for the developing of set measures for reducing the temperature regime of containing products produced from cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the course of the research study it was discovered that at the increased temperature (40 °C) of the storage of samples on the basis of cement binder the almost linear increase in intensity of heat evolution at the early stages of hydration by an increase in the dosage of the admixture of lithium carbonate (Li2CO3) entered into the composition of the mixture within the studied range of dosages from 0.5% to 2.5% is observed. Taking into account the experimental data [8] obtained earlier by the group of authors about the increase in the efficiency of the effect of this admixture on the speed of the exothermic reaction at the increased temperature regime of the storage of samples, it is possible to draw a conclusion that the admixture of the lithium carbonate has the potential of being used for the solving of the problem of decreasing the energy capacity of the process of the thermal treatment of the concrete products and constructions during their manufacture in plant conditions. In the event that the subsequent researches of the physical and mechanical characteristics and the characteristics of durability of the control samples studied within the present research show the positive results, it will allow to provide the energy saving at the hydrothermal processing of the concrete constructions by reducing the time or decreasing the temperature of processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of the research study it was discovered that at the increased temperature (40 °C) of the storage of samples on the basis of cement binder the almost linear increase in intensity of heat evolution at the early stages of hydration by an increase in the dosage of the admixture of lithium carbonate (Li2CO3) entered into the composition of the mixture within the studied range of dosages from 0.5% to 2.5% is observed. Taking into account the experimental data [8] obtained earlier by the group of authors about the increase in the efficiency of the effect of this admixture on the speed of the exothermic reaction at the increased temperature regime of the storage of samples, it is possible to draw a conclusion that the admixture of the lithium carbonate has the potential of being used for the solving of the problem of decreasing the energy capacity of the process of the thermal treatment of the concrete products and constructions during their manufacture in plant conditions. In the event that the subsequent researches of the physical and mechanical characteristics and the characteristics of durability of the control samples studied within the present research show the positive results, it will allow to provide the energy saving at the hydrothermal processing of the concrete constructions by reducing the time or decreasing the temperature of processing.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that firstly, this admixture meets the requirements listed above, and secondly, the recent researches [8] have shown that when it is used in combination with cements of domestic production, it is possible to observe the improvement of the efficiency of the admixture's effect with rising temperature regime of the storage of samples, which is capable to provide the additional synergetic effect of the introduction of the considered accelerator in the conditions of the hydrothermal processing applied by manufacture of the reinforced concrete products in plant conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Application of modern methods of PC condition parameters definition for prediction of its activity dies not reduce the importance of direct PC behavior control in the course of its water mixing and setting [7][8][9]. The necessity of such control is connected with changing concrete mix treatment easiness depending on applied PC structure forming capacity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…One of such additives can be lithium carbonate (Li2CO3). At the same time, according to the authors' studies [6] it has been established that unlike most other known accelerator additives, lithium carbonate significantly increases the intensity of the exothermic hydration reaction of individual Portland cement samples not only at normal and lower temperatures, but also at a higher temperature corresponding to the conditions of heat treatment in the manufacture of reinforced concrete products in the factory.…”
Section: Introductionmentioning
confidence: 99%